2008
DOI: 10.1080/08860220802132171
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Quadruple Therapy in Childhood Diffuse Proliferative Lupus Nephritis

Abstract: In this study, we evaluated the frequency, clinical presentation, treatment protocols, prognostic factors, and outcome in children with diffuse proliferative lupus nephritis (DPLN). Between June 1990 and December 2004, 46 patients were diagnosed to have systemic lupus erythematosus (SLE), and 26 of them (56.5%) were found to have DPLN. Renal manifestations were present in 25 patients, and the majority of them presented with severe renal findings, such as nephrotic syndrome and renal failure. All patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…To date, the only study comparing MMF to CYC for induction of remission in childhood lupus nephritis showed superiority of the former for class III nephritis [75][76][77][78][79][80][81][82][83][84][85][86]. However, despite showing efficacy in membranous nephropathy, MMF failed to attenuate disease progression in pediatric patients with class IV nephritis [87].…”
Section: Lupus Nephritismentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the only study comparing MMF to CYC for induction of remission in childhood lupus nephritis showed superiority of the former for class III nephritis [75][76][77][78][79][80][81][82][83][84][85][86]. However, despite showing efficacy in membranous nephropathy, MMF failed to attenuate disease progression in pediatric patients with class IV nephritis [87].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…In an attempt to overcome the obstacle of CYC-induced side effects, a quadruple therapy protocol may be employed, although, again, there are no randomized data to support its generalized use [85]. To date, the only study comparing MMF to CYC for induction of remission in childhood lupus nephritis showed superiority of the former for class III nephritis [75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…During follow-up (median 4.5 years), no significant differences were found for any outcome measures including normal serum creatinine at last follow-up (86% in all patients), renal flares (45%), median time to renal flare (36 months in AZA, 20 months in IV-CY, 12 months in the steroids group, P=0.15), and overall renal survival (97% in AZA, 89% in IV-CY, 75% in the steroids group, P=0.38). The authors concluded that AZA and IV-CY were equally efficacious in the treatment of acute renal failure in pediatric lupus nephritis [38,39].…”
Section: Cy In Pediatric Lupus Nephritismentioning
confidence: 96%
“…Demircin et al [38] treated 19 children with diffuse proliferative (class IV) lupus nephritis (65% had proteinuria >40 mg m −2 h −1 and hypoalbuminemia, 62% had impaired renal function) with a multi-drug therapy consisting of six to 12 monthly pulses of IV-MP (30 mg kg −1 day −1 , maximum 1 g) given consecutively for 3 days, followed by oral administration of prednisone, oral administration of CY (2 mg/kg) for 2-3 months, followed by AZA (0.2 mg/kg) and dipyridamole (5 mg kg −1 day −1 ). Maintenance therapy included low-dose oral administration of prednisone, dipyridamole, and AZA for at least 5 years.…”
Section: Cy In Pediatric Lupus Nephritismentioning
confidence: 98%
“…Cyclophosphamide Cyclophosphamide (CYC) has been the most frequently used drug for decades in the induction therapy of LN, which was initially used in oral form (1-3 mg/kg/day) [4,16]. After intravenous (IV) CYC was introduced and was shown to be superior to daily oral CYC, induction protocols in most…”
Section: Induction Therapymentioning
confidence: 99%